Hubungan Usia Kehamilan Ibu Dengan Status Nutrisi Pada Balita Di Wilayah Kerja Puskesmas Undaan Kabupaten Kudus - Pannes David Sahri, Pannes David Sahri; Umi Faridah; Indanah, Indanah (CV. Ulil Albab Corp, 2025)
The development of nutritional status in toddlers is greatly influenced by various factors, one of which is the mother's gestational age. The relationship between the mother's gestational age and the nutritional status of toddlers is one of the important aspects in child growth. This study aims to determine the relationship between the mother's gestational age and the nutritional status of toddlers in the Undaan Health Center work area, Kudus Regency. This type of research is a correlational analytical study with a cross-sectional approach. The sample used in this study was 68 toddlers taken using a purposive sampling technique. Data were collected through observation, maternal gestational age questionnaires and nutritional status questionnaires, and anthropometric measurements to determine the nutritional status of toddlers. Data analysis was carried out using the Chi-Square test to evaluate the relationship between maternal gestational age and toddler nutritional status. The results showed that there was a significant relationship between maternal gestational age and toddler nutritional status, with a p value = 0.002 (p> 0.05) and a correlation coefficient of 0.370. Thus, this study provides important insights into the factors that influence the nutritional status of toddlers. The conclusion shows that there is a significant relationship between maternal gestational age and nutritional status in toddlers in the Undaan Health Center work area, Kudus Regency in 2025.